Detection of 19-bp indel of PLAG1 gene and its effects on morphometric traits in indigenous and crossbred cattle of Bangladesh (Bangladesh Journal of Animal Science, 2022)
Stature and live weight are economically important traits in livestock species and polygenic in nature. Pleomorphic adenoma gene 1 (PLAG1) is a member of the PLAG family of zinc finger transcription factors which has a specific association with growth related traits in human and various livestock species including cattle. This study investigated the 19-bp indel (insertion/deletion) polymorphism of the PLAG1 gene and its possible association with morphometric traits in indigenous and Holstein-Local (H×L) crossbred cattle of Bangladesh. A total of 160 blood samples were collected from the aforementioned cattle populations whereas data on morphometric traits were recorded only from H×L crossbreds. PCR amplification fragment harboring 19-bp indel detected three genotypes II (366 bp), ID (366/347 bp) and DD (347 bp). The II, ID and DD genotype frequencies were 0.00, 0.09 and 0.91 respectively in indigenous cattle populations and the corresponding frequencies were 0.14, 0.43 and 0.43, respectively in H×L crossbred populations. None of the investigated morphometric traits had a significant association with 19-bp indel genotypes. However, non-genetic factors such as herd, year and parity had significant effects only on hip height trait in crossbred cattle (P